Model Media Video TikTok Berbasis Cerita dan Quotes dalam Pembentukan Karakter Islam di PAUD RA. Kartini Sebatik Barat - Hasanuddin; Iqbal Irfansyah; Nursufia Cahaya; Nur Liana (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2024)
The development of digital technology has provided new opportunities in the world of education, including in forming the character of early childhood. TikTok, as a popular social media platform, can be used as an innovative learning medium, especially in instilling Islamic values through story and quote-based videos. This research aims to analyze the effectiveness of using TikTok videos based on stories and quotes in forming the Islamic character of early childhood in PAUD R.A. Kartini Sebatik Barat. The research method used is qualitative research with a descriptive approach. Data was obtained through observation, interviews with educators, and analysis of video content used in learning. The research results show that the use of TikTok videos based on Islamic stories and quotes can increase children’s understanding of Islamic character values, such as honesty, patience and caring. Children are more interested and easier to understand moral concepts through interactive visual media that fits their digital world. However, challenges in implementing this method include limited access to technology for some educators and the need for supervision in the use of social media so that it remains in accordance with the principles of Islamic education. This research concludes that the use of TikTok as a learning medium based on Islamic stories and quotes has great potential in shaping the character of young children if applied with the right approach and adequate supervision. It is hoped that these findings can be a reference for educators and parents in developing technology-based learning methods that are in accordance with Islamic values in the digital era.